Originally Posted by

**Ingersoll** The first is **2x-1=y**

Simple enough: y=0, and say x=1. Then two minus one equals 1 for **(1,0)** Mr F says: When y = 0, x = 1/2. (2x - 1 = 0 => 2x = 1 => x = 1/2).

Now x=0 so it's -1 divided by y for negative 1 for **(0,-1)**.

These create a straight line that graphs perfectly.

1. I am doing this right, right?

2. My second issue here is that I can't find a checkpoint for the above to save my life. Nothing makes sense... which in turn leads me to believe I'm not doing this right.

Please help. Thank you.

Oh, also: Graph **3y=-5** Mr F says: Is this the complete equation? As written, y - -5/3 which is a horizontal line passing through y = -5/3.

I understand y=3 or x=1, but I don't get how and why a horizontal line below the x-axis is formed from this. There's no explanation in the book and it wasn't covered in class today. Homework for this section gets turned in right before the test for this section on Tuesday when we come back from the weekend.

Again, thank you for your help. It is greatly appreciated.